Manajemen Resiko Teknologi Infor Manajemen Resiko Teknologi Informasi terhadap Audit Internal dan Dampak yang Ditimbulkan : Manajemen Resiko Teknologi Informasi Terhadap Audit Internal dan Dampak Yang Ditimbulkan - Febryana Dewi Artati; Ficky Andrianto; Maria Ulfa; Novi Khoiriawati (STEI Kanjeng Sepuh Gresik Jawa Timur, 2022)
In this research, researchers will analyze the use of information technology in the internal audit process and the impact it causes, both good and bad impacts. This analysis process uses descriptive qualitative methods with literacy studies through journals and articles related to internal audit. Researchers will use the journal or article by comparing and matching data from existing research results. After the data is collected, the researcher will draw conclusions from the data obtained. The result of this research is that the use of information technology has an impact on the internal audit process. There are good and bad impacts, including the ease of auditing process and speed when auditing large amounts of data. However, the bad impact is that the command input error on the computer makes the audit process repeat itself, besides that auditors still need to re-examine the results of computer audits because computer audit results are not always accurate. Damage that may occur to the device can also affect the auditing process.